2007
DOI: 10.20377/jfr-302
|View full text |Cite
|
Sign up to set email alerts
|

Zeitverwendung und Arbeitsteilung in Paarhaushalten

Abstract: Household tasks are still unequally distributed in industrialized countries whereby most of the work is frontloaded to women. The aim of the article is to explain the unequal distribution using microeconomic models and referring to social norms and institutions. The household production approach, the household bargaining approach and the gender display approach are empirically tested in random-effects regressions using the data of the German Time Budget Survey 2001/2002. Economic determinants are major predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
5
0
6
Order By: Relevance
“…Akerlof and Kranton (2000) have modelled such costs as "identity-utility"-loss. The studies of Bittman et al (2003), Haberkern (2007) and Beblo and Robledo (2008) cited earlier provide empirical support for this notion: the desire to comply with gender-specific social norms in heterosexual households may indeed have effects on how males and females divide household work. Women who violate the ruling social norms by contributing a larger share to the household's income than their male partner must "pay" a penalty for their violation by also (re-) increasing their share in housework.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Akerlof and Kranton (2000) have modelled such costs as "identity-utility"-loss. The studies of Bittman et al (2003), Haberkern (2007) and Beblo and Robledo (2008) cited earlier provide empirical support for this notion: the desire to comply with gender-specific social norms in heterosexual households may indeed have effects on how males and females divide household work. Women who violate the ruling social norms by contributing a larger share to the household's income than their male partner must "pay" a penalty for their violation by also (re-) increasing their share in housework.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, the gap in time spent on household-related activities appears to be influenced by the share women contribute to overall household income: For example, Beblo and Robledo (2008) show a woman's relative bargaining power to increase the more she specializes in labor market production. Bittman et al (2003) and Haberkern (2007), using time-use data from Australia and Germany, respectively, show that women are able to reduce their workload in the household when increasing the share they contribute to the monetary income of the household, until these contributions are equal. But strikingly, when women contribute even more, their household-related workload increases again.…”
Section: Related Literaturementioning
confidence: 99%
“…When the wife earns more, her share of housework goes up again. Haberkern (2007) showed that wives react stronger to a violation of traditional gender roles than husbands in Germany. Wives who become the primary breadwinner do more housework in order to emphasize their identity as a homemaker.…”
Section: Non-market Work and Relative Incomementioning
confidence: 99%
“…2020 ; Geißler 2014 , S. 398 ff. ; Haberkern 2007 ; Becker-Schmidt 2008 ). Nur etwa 10 % der Mütter haben zudem selbst den Eindruck, dass ihr Engagement von der Gesellschaft anerkannt wird (IfD Allensbach 2013 , S. 75, 79).…”
Section: Introductionunclassified
“…( 2015 ), Alwin et al. ( 1992 ), Kurz ( 1998 ), Haberkern ( 2007 ), Ebner et al. ( 2020 ) und Mandel et al.…”
unclassified